2018
DOI: 10.7196/samj.2018.v108i3.12635
|View full text |Cite
|
Sign up to set email alerts
|

High positive computed tomography yields in the emergency department might not be a positive finding

Abstract: Background. There is growing pressure to reduce unnecessary computed tomography (CT) imaging requests that the radiology department receives from the emergency department (ED); however, information on acceptable usage rates and diagnostic yields remains scanty. Objectives. To describe the indications, clinical categories and positive yield rates of patients receiving CT scans in the ED. Methods. A retrospective record review was done of all patients who received CT scans at an urban, adult academic ED during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 25 publications
2
14
1
Order By: Relevance
“…The positivity rate may be considered too high, indicating likely underdiagnosis because of resource constraints. 1 The audit showed that the waiting time for CT scans was dramatically reduced, whilst the number of CT scans remained more or less the same and the number of inappropriate requests was also reduced. All CT scan bookings were deemed appropriate (Table 1).…”
Section: Intervention: Access and Governance Of A Ct Scan Servicementioning
confidence: 99%
See 1 more Smart Citation
“…The positivity rate may be considered too high, indicating likely underdiagnosis because of resource constraints. 1 The audit showed that the waiting time for CT scans was dramatically reduced, whilst the number of CT scans remained more or less the same and the number of inappropriate requests was also reduced. All CT scan bookings were deemed appropriate (Table 1).…”
Section: Intervention: Access and Governance Of A Ct Scan Servicementioning
confidence: 99%
“…The positivity rate may be considered too high, indicating likely underdiagnosis because of resource constraints. 1 …”
Section: Example 1: Access To and Clinical Governance Of Computer Tomographic Scansmentioning
confidence: 99%
“…EPs prefer the least invasive methods for diagnosis. [ 1 ] X-ray radiography, ultrasonography, computed tomography (CT), and magnetic resonance imaging are frequently used in EDs. The use of CT in EDs is widespread, as CT is a fast imaging method and expedites ED procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The use of CT in EDs is widespread, as CT is a fast imaging method and expedites ED procedures. [ 1 2 ] Although CT has become increasingly common, the accurate interpretation of CT requires a high level of knowledge. To avoid misinterpretations, the radiologist interpreting the CT scan needs to be familiar with the clinical condition of the patient.…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, usage increased by more than 300% from 1996 to 2007 with a more recent study in Taiwan showing an increase of 160% from 2009 to 2013 [5,6]. In South Africa, 45 million people utilize public sector healthcare services where there are 5 CT scanning machines available per one million population -it is a finite and costly resource [7][8][9]. This is dwarfed by developed countries such as Japan and the USA who have 111 and 42 CT scanners per million population, respectively [7][8][9].…”
Section: Introductionmentioning
confidence: 99%